Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1097/mph.0b013e318257dc91
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of an Adolescent With Locally Advanced Cervicovaginal Clear Cell Adenocarcinoma Using Definitive Chemotherapy and Radiotherapy

Abstract: Pediatric cervicovaginal clear cell adenocarcinoma (CCA) is rare but continues to occur in the postdiethylstilbestrol era. Ideal management is unclear. We report a case of locally advanced, node-negative CCA in a 14-year-old girl without a history of diethylstilbestrol exposure. The patient's disease was FIGO stage IIIA, involving the cervix, vagina, and parametrium. She was treated with concurrent cisplatin and external beam radiation, followed by interstitial low-dose rate brachytherapy. The patient has no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Ansari et al 47 and Chan et al 48 reported cases that showed a benefit from chemotherapy or radiotherapy in CCAC, but no prospective clinical trial exists to confirm or refute their data.…”
Section: Molecular Biology and Geneticsmentioning
confidence: 99%
“…Ansari et al 47 and Chan et al 48 reported cases that showed a benefit from chemotherapy or radiotherapy in CCAC, but no prospective clinical trial exists to confirm or refute their data.…”
Section: Molecular Biology and Geneticsmentioning
confidence: 99%
“…In these patients, fertility preservation is still associated with unfavorable pregnancy outcomes due to radiation-induced damage to the uterine and myometrial vessels, with increased risks of preterm labor and normal fetal growth alterations [ 44 ]. Infertility is frequently associated with high levels of stress, depression, and anxiety [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…While most of the available data refer to patients with early stage disease which are usually triaged to RS and eventual adjuvant CT/RT, there is little experience in locally advanced stage patients [9]; more recently, based on the level I evidence on the superiority of exclusive chemoradiation, this bimodal approach has also been attempted in 2 cases of adolescents bearing stage III CCAC of the uterine cervix [6,7]. …”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of this disease remains elusive: the association between in utero exposure to diethylstilbestrol and occurrence of CCAC of the lower female genital tract has been acknowledged since the early 1970s [3], but evidence has also been reported that genetic and exogenous factors, HPV infection as well as p53 mutation can be also involved in CCAC natural history [4,5]. Given the rarity of the disease, optimal treatment management is far from being defined and currently follows the same approaches employed for more common histotypes: in early stage disease, radical surgery (RS) followed by adjuvant chemoradiation (CT/RT) in case of high-risk pathological findings is usually utilized [5], while different therapeutic strategies, including exclusive CT/RT, have been employed in locally advanced CCAC patients [5,6,7]. Although data about clinical outcome remain controversial [8,9], some studies suggest that prognosis of patients bearing cervical CCAC or other variants of uterine cervical adenocarcinoma is worse compared to squamous cell tumors [5,10,11], thus making the investigation of multimodal treatment strategies clinically worthwhile.…”
Section: Introductionmentioning
confidence: 99%